Challenges in managing osteogenesis imperfecta in a resource-limited setting: a case report - Ssekabembe Richard; Natumanya Robert; Vanusa Da Consolação Sambo; Abonga Daniel; Okidi Ronald (Journal of Medical Case Reports)
Abstract Introduction Osteogenesis imperfecta is a rare inherited connective tissue disorder that results in excessive bone fragility due to defects in collagen production. The majority of osteogenesis imperfecta cases are inherited in an autosomal dominant pattern, and 17 genetic causes have been identified. Diagnosis is usually based on clinical presentation and low bone mineral density scores, while treatment involves a multidisciplinary approach using medical therapies such as bisphosphonates, vitamin C, and pamidronate. Recent research has also explored new therapies, including teriparatide, denosumab, and allele-specific silencing (Edelu et al. in Ann Med Health Sci Res 4(Suppl 1):S1–5, 2014; Bastos et al. in Einstein (São Paulo) 8:480–2, 2010; Van Dijk and Sillence in Am J Med Genet A 164A(6):1470–81, 2014; Subramanian and Viswanathan in Osteogenesis Imperfecta. In: StatPearls. Treasure Island (FL): StatPearls Publishing. http://www.ncbi.nlm.nih.gov/books/NBK536957/ . Accessed 2 Mar 2023, 2022). Case presentation A 3-week-old female neonate of African ethnicity was delivered at term by emergency C-section due to two previous scars. The baby had an APGAR score of 7 at 5 minutes and a birth weight of 2.5 kg. The neonate had short and deformed limbs, a soft head, and bluish eyes. The neonate was diagnosed with osteogenesis imperfecta on the basis of clinical examination findings and radiological investigations, which showed multiple bony discontinuities at variable stages of healing in the limbs and ribs. The neonate was managed with supplemental oxygen by nasal prongs and intravenous antibiotics but unfortunately passed away before being reviewed by the orthopedic team. Conclusion This case report underscores the importance of early diagnosis of osteogenesis imperfecta and highlights the need for increased clinical awareness, specialized training, and resource allocation to improve outcomes for patients with rare genetic disorders in low-resource settings.